A first principle study to investigate structural, electronic and optical properties of pristine and valency comparable Co, P decorated graphene like boron nitride (BN) nanosheets. (2nd December 2022) - Milon; Hossain, Md Kamal; Roy, Debashis; Ahmed, Farid
ABSTRACT: In this ongoing research work, a density functional theory (DFT) study has been performed to investigate the structural, chemical, electrical, and optical properties of the boron nitride nanosheets (BNNSs) by replacing one boron atom from BNNSs with valency comparable Cobalt (Co) and Phosphorus (P) atoms. The order of the calculated cohesion energy is −5.96 > −5.82 > −5.81 eV, respectively, for BN, Co@BN and P@BN, which leads to good structural stability. The calculated Eg follows the order 6.82 > 5.84 > 3.82 eV respectively for BN, P@BN and Co@BN, which reveal evidence of enhancing the electrical properties of the doped structures. Vibrational spectroscopies, global descriptors-DFT parameters, DOS, MEP and absorption spectra gave details information about the enhancement of the various properties of the BN nanosheets by doping, and suggest a high range of application in technology.